Negative plate and preparation method thereof, battery and power utilization device
By using liquid-retaining polymers and lithium ions with different molecular weights in the active layer of the negative electrode sheet, the problem of slowing lithium ion migration caused by electrolyte swelling is solved, the cycle performance and magnification of the battery is improved, and the new energy industry is satisfied with the high performance demand.
Patent Information
- Application Number
- CN202310799088.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The circulation performance and charging rate of traditional secondary batteries are difficult to meet the demand for high performance in the new energy industry, especially in negative electrode sheets, the swelling of the electrolyte causes the migration of lithium ions to slow down, affecting battery performance.
Using the active layer on the surface of the current collector, the active layer contains at least two liquid-retaining polymers with different molecular weights, which can form hydrogen bonds with water, and regulate the mass ratio of liquid-retaining polymers with different molecular weights and lithium ions. The content improves the consistency of the active layer of the negative electrode sheet and the cycling performance and magnification of the battery.
Effectively maintain the smooth transmission of active ions, reduce the blockage caused by electrolyte swelling, improve the cycling performance and magnification of the battery, and enhance the migration rate of lithium ions.
Smart Images

Figure CN119230827A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a preparation method thereof, a battery, and an electrical device. Background Art
[0002] Secondary batteries are increasingly widely used due to their clean and renewable characteristics. They mainly rely on the movement of active ions such as lithium ions between the positive and negative electrodes to generate electrical energy.
[0003] In recent years, with the rapid development of the new energy industry, people's demand for electric vehicles, electric bicycles and other electrical devices has increased, and their performance requirements have become higher and higher.
[0004] As demand increases, the performance of traditional secondary batteries is increasingly unable to meet people's needs and needs further improvement. Summary of the invention
[0005] Based on this, it is necessary to provide a negative electrode sheet and a preparation method thereof, a battery, and an electrical device, aiming to improve the cycle performance and rate of the battery.
[0006] In a first aspect of the present application, a negative electrode sheet is provided, the negative electrode sheet comprising a current collector and an active layer disposed on a surface of the current collector, wherein components of the active layer include at least two liquid-retaining polymers having different molecular weights;
[0007] The liquid retaining polymer contains functional groups that can form hydrogen bonds with water.
[0008] The active layer in the above-mentioned negative electrode sheet contains at least two liquid-retaining polymers with different molecular weights. When used to prepare a battery, on the one hand, the liquid-retaining polymer in the negative electrode sheet can adsorb the electrolyte to keep the active ion transmission unobstructed. On the other hand, the combination of at least two liquid-retaining polymers with different molecular weights can reduce the degree of blockage of pores caused by swelling of the liquid-retaining polymer due to adsorption of electrolyte, thereby slowing down the migration of active ions, while maintaining a high liquid absorption effect. All aspects work together to improve the cycle performance and rate of the battery.
[0009] In some embodiments, the liquid-retaining polymer in the active layer has at least two peaks in its gel chromatography elution curve.
[0010] In some embodiments, in the gel chromatography elution curve, the number average molecular weight corresponding to each peak is independently selected from 50 to 600;
[0011] Optionally, the number average molecular weight corresponding to at least one peak is 50-100, and the number average molecular weight corresponding to at least another peak is 300-600.
[0012] By controlling the synergy of at least two specific liquid-retaining polymers in different molecular weight ranges, the consistency of the active layer of the negative electrode sheet can be further improved, and the cycle performance and rate of the battery can be improved.
[0013] In some of the embodiments, the mass ratio of the liquid retaining polymer with a number average molecular weight of 50-100 to the liquid retaining polymer with a number average molecular weight of 300-600 is 1:(1-6).
[0014] In some embodiments, the gel chromatography elution curve of the liquid retaining polymer in the active layer contains three peaks.
[0015] The gel chromatography elution curve of the liquid-retaining polymer in the active layer contains three peaks, which actually means that the active layer contains at least three liquid-retaining polymers with different molecular weights; further, by combining at least three liquid-retaining polymers with different molecular weights within a specific molecular weight, the cycle performance and rate of the battery are further improved.
[0016] In some embodiments, the active layer includes a first liquid-retaining polymer having a number average molecular weight of T1, a second liquid-retaining polymer having a number average molecular weight of T2, and a third liquid-retaining polymer having a number average molecular weight of T3;
[0017] Among them, 50≤T1≤100, 100<T2≤250, 250<T3≤600; optionally, 500≤T3≤600.
[0018] By combining three liquid-retaining polymers in a specific molecular weight range, on the one hand, while maintaining a relatively high liquid absorption effect, the degree to which the liquid-retaining polymer blocks the pores and slows down the migration of active ions due to swelling caused by adsorption of electrolyte can be reduced; on the other hand, the liquid-retaining polymer with a smaller molecular weight also has a certain mobility, which can further improve the consistency of the active layer of the negative electrode sheet and improve the cycle performance and rate of the battery.
[0019] In some embodiments, the mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer is (1-2): (1-4): (3-6);
[0020] Optionally, a mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer is 1:(1-4):(5-6).
[0021] By adjusting the mass ratio of three liquid-retaining polymers with different molecular weights, the cycle performance and rate of the battery can be further improved.
[0022] In some of these embodiments, at least one liquid retaining polymer contains lithium ions;
[0023] The presence of lithium ions can further increase the migration rate of lithium ions between the positive and negative electrodes. The liquid-retaining polymer contains lithium ions, that is, the lithium ions are connected to other elements on the molecular chain of the liquid-retaining polymer by forming chemical bonds. In this way, lithium ions are not easy to leak, which effectively increases the migration rate of lithium ions between the positive and negative electrodes, thereby improving the cycle performance and rate of the battery.
[0024] Optionally, based on the mass of the liquid retaining polymer, the mass proportion of the lithium ions is 0.2% to 15%.
[0025] By regulating the mass ratio of lithium ions in the liquid-retaining polymer, the migration rate of lithium ions between the positive and negative electrodes can be further improved, thereby improving the cycle performance and rate of the battery.
[0026] In some of these embodiments, at least one of the liquid-retaining polymers has lithium ions on its side groups on its molecular chain;
[0027] Optionally, the mass ratio of the liquid-retaining polymer containing lithium ions to the liquid-retaining polymer not containing lithium ions is 10:(2-5).
[0028] In some of the embodiments, in the active layer, the total mass of the liquid-retaining polymer accounts for 0.3% to 0.8%;
[0029] Optionally, in the active layer, the total mass proportion of the liquid-retaining polymer is 0.3% to 0.5%.
[0030] The amount of liquid-retaining polymer used can be adjusted to reduce the chance of gelling during preparation, leading to decreased electrode uniformity.
[0031] In some embodiments, the liquid retaining polymer satisfies at least one of the following conditions (I) to (II):
[0032] (I) the functional group includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group and an ether bond;
[0033] Optionally, each of the liquid-retaining polymers contains the same functional group;
[0034] (II) each of the liquid-retaining polymers has a main chain with the same structure;
[0035] Optionally, the main chain is selected from any one of a polyethylene glycol main chain, a polyvinyl alcohol main chain and a polyacrylic acid main chain.
[0036] In some of the embodiments, the liquid-retaining polymer includes at least one of polyvinyl alcohol free of lithium ions, polyvinyl alcohol containing lithium ions, polyethylene glycol free of lithium ions, polyethylene glycol containing lithium ions, polyacrylic acid free of lithium ions, polyacrylic acid containing lithium ions, polyvinyl alcohol-acrylic acid graft polymer free of lithium ions, polyvinyl alcohol-acrylic acid graft polymer containing lithium ions, polyethylene glycol acrylate free of lithium ions, polyethylene glycol acrylate containing lithium ions, polyethylene glycol diacrylate free of lithium ions, polyethylene glycol diacrylate containing lithium ions, polyethylene glycol acrylate free of lithium ions, and polyethylene glycol acrylate containing lithium ions.
[0037] In some embodiments, the active layer further comprises a binder;
[0038] Optionally, the binder includes a carboxymethyl cellulose binder, and in the active layer, the total mass of the carboxymethyl cellulose binder and the liquid-retaining polymer accounts for 1% to 2%;
[0039] Further optionally, the total mass proportion of the carboxymethyl cellulose binder and the liquid retaining polymer is 1% to 1.5%.
[0040] By controlling the amount of carboxymethyl cellulose binder, it can work synergistically with the liquid-retaining polymer to maintain good liquid-retaining performance while maintaining good bonding performance to reduce the probability of electrode cracking.
[0041] In some of these embodiments, the molecular weight of the binder is different from the molecular weight of the liquid retaining polymer;
[0042] Optionally, the number average molecular weight of the binder is greater than the molecular weight of the liquid retaining polymer;
[0043] Further optionally, the number average molecular weight of the binder is ≥ 100,000.
[0044] A second aspect of the present application provides a method for preparing a negative electrode sheet, comprising the following steps:
[0045] An active layer is formed on the surface of a current collector using an active slurry to prepare a negative electrode sheet;
[0046] The components of the active slurry include at least two liquid-retaining polymers with different molecular weights; the liquid-retaining polymers contain functional groups that can form hydrogen bonds with water.
[0047] According to a third aspect of the present application, a battery is provided, wherein the battery comprises the negative electrode sheet of the first aspect or the negative electrode sheet prepared by the method for preparing the negative electrode sheet of the second aspect.
[0048] According to a fourth aspect of the present application, there is provided an electrical device, wherein the electrical device comprises the battery according to the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0050] Figure 1 is a schematic diagram of one embodiment of a battery;
[0051] Figure 2 yes Figure 1 Exploded diagram of
[0052] Figure 3 is a schematic diagram of an embodiment of a battery pack;
[0053] Figure 4 yes Figure 3 Exploded diagram of
[0054] Figure 5 is a schematic diagram of an embodiment of an electrical device in which a battery is used as a power source.
[0055] Description of reference numerals:
[0056] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery; 41. Shell; 42. Electrode assembly; 43. Cover plate; 5. Electrical device. DETAILED DESCRIPTION
[0057] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0058] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0059] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0060] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0061] In summary, the performance of traditional batteries is increasingly unable to meet people's needs. With the rapid development of the new energy industry, people have higher and higher requirements on the cycle performance and charging rate of batteries.
[0062] Technicians mainly focus on developing new active materials, but the development of new materials is a long and arduous process, and no substantial progress has been made so far. Some technical studies have found that during the operation of the battery, the gaps in the negative electrode sheet need to be filled with electrolyte to form a lithium ion liquid phase transmission channel, but during the cycle charge and discharge process, the electrolyte impregnated and filled in the pores of the negative electrode sheet will be squeezed out or deposited at the bottom of the battery cell due to gravity, resulting in insufficient electrolyte during the battery cell cycle and thus reducing the battery cell cycle performance.
[0063] Therefore, technicians tried to introduce polymers with high liquid absorption into the negative electrode sheet to improve the liquid retention of the negative electrode sheet; however, the technicians further found that polymers with high liquid absorption will inevitably swell after absorbing liquid, and the swelling of the polymer will block the pores of the active layer of the negative electrode sheet, which will slow down the migration of lithium ions and have a negative impact on battery performance.
[0064] Based on this, after a lot of creative exploration, the negative electrode sheet in this application was obtained that can improve the charging rate and cycle performance of the battery.
[0065] In one embodiment of the present application, a negative electrode sheet is provided, which includes a current collector and an active layer disposed on the surface of the current collector, wherein the components of the active layer include at least two liquid-retaining polymers with different molecular weights; the liquid-retaining polymer contains functional groups that can form hydrogen bonds with water.
[0066] The active layer in the above-mentioned negative electrode sheet contains at least two liquid-retaining polymers with different molecular weights. When used to prepare a battery, on the one hand, the liquid-retaining polymer in the negative electrode sheet can adsorb the electrolyte to keep the active ion transmission unobstructed. On the other hand, the combination of at least two liquid-retaining polymers with different molecular weights can reduce the degree of blockage of pores caused by swelling of the liquid-retaining polymer due to adsorption of electrolyte, thereby slowing down the migration of active ions, while maintaining a high liquid absorption effect. All aspects work together to improve the cycle performance and rate of the battery.
[0067] It should be noted that the current collector in the negative electrode sheet has two surfaces opposite to each other in the thickness direction thereof, and the active layer can be disposed on any one or both of the two opposite surfaces of the current collector.
[0068] In some of the embodiments, the liquid retaining polymer in the active layer has at least two peaks in its gel chromatography elution curve.
[0069] It can be understood that a peak of the gel chromatography elution curve represents a specific molecular weight or molecular weight range, and the gel chromatography elution curve of the liquid-retaining polymer in the active layer contains at least two peaks, that is, the components characterizing the active layer include at least two liquid-retaining polymers with different molecular weights.
[0070] In some of the embodiments, the gel chromatography elution curve of the liquid retaining polymer in the active layer contains two peaks.
[0071] Optionally, the number average molecular weight of the liquid-retaining polymer corresponding to each peak is independently selected from 50 to 600.
[0072] In some of the embodiments, at least one peak corresponds to a number average molecular weight of 50-100, and at least another peak corresponds to a number average molecular weight of 300-600.
[0073] In some of the embodiments, at least one peak corresponds to a number average molecular weight of 50-100, and at least another peak corresponds to a number average molecular weight of 500-600.
[0074] By controlling the synergy of at least two specific liquid-retaining polymers in different molecular weight ranges, the consistency of the active layer of the negative electrode sheet can be further improved, and the cycle performance and rate of the battery can be improved.
[0075] Optionally, the active layer includes a liquid-retaining polymer having a number average molecular weight of 50-100 and a liquid-retaining polymer having a number average molecular weight of 300-600.
[0076] In one embodiment, the mass ratio of the liquid retaining polymer with a number average molecular weight of 50-100 to the liquid retaining polymer with a number average molecular weight of 300-600 is 1:(1-6).
[0077] In some embodiments, the active layer includes a liquid retaining polymer having a number average molecular weight of 50-100 and a liquid retaining polymer having a number average molecular weight of 500-600.
[0078] In one embodiment, the mass ratio of the liquid retaining polymer with a number average molecular weight of 50-100 to the liquid retaining polymer with a number average molecular weight of 500-600 is 1:(1-6).
[0079] In the above "1: (1~6)", the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 1:1, 1:2, 1:3, 1:4, 1:5, 1:6; or a range consisting of any two values, for example: 1: (1~5), 1: (1~4), 1: (1~3), 1: (1~2), 1: (2~6), 1: (2~5).
[0080] In some of the embodiments, the gel chromatography elution curve of the liquid retaining polymer in the active layer contains three peaks.
[0081] The fact that the gel chromatography elution curve of the liquid-retaining polymer contains three peaks essentially means that the liquid-retaining polymer contains at least three different molecular weights.
[0082] Furthermore, the area ratio of each peak is calculated through integration and homogenization processing using software supporting the gel chromatography, that is, the mass ratio of polymers of specific molecular weight corresponding to each peak.
[0083] It is understood that the above molecular weight can be any one of number average molecular weight, weight average molecular weight, viscosity average molecular weight and Z average molecular weight.
[0084] Optionally, the number average molecular weights of the liquid-retaining polymers corresponding to the three peaks are independently selected from 50 to 600.
[0085] Furthermore, by combining at least three liquid-retaining polymers with different molecular weights within a specific molecular weight, the cycle performance and rate of the battery are further improved.
[0086] In some embodiments, the active layer includes a first liquid-retaining polymer with a number average molecular weight of T1, a second liquid-retaining polymer with a number average molecular weight of T2, and a third liquid-retaining polymer with a number average molecular weight of T3.
[0087] Among them, 50≤T1≤100, 100<T2≤250, 250<T3≤600.
[0088] In some of these embodiments, 300≤T3≤600.
[0089] Optionally, 500≤T3≤600.
[0090] By combining three liquid-retaining polymers in a specific molecular weight range, on the one hand, while maintaining a relatively high liquid absorption effect, the degree to which the liquid-retaining polymer blocks the pores and slows down the migration of active ions due to swelling caused by adsorption of electrolyte can be reduced; on the other hand, liquid-retaining polymers with a smaller molecular weight have a certain mobility, which can further improve the consistency of the active layer of the negative electrode sheet and improve the cycle performance and rate of the battery.
[0091] In the above “50≤T1≤100”, the value of T1 includes the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiment and the following point values: 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 99, 100; or a range consisting of any two values, for example: 50-55, 50-60, 50-65, 50-70, 50-75, 50-80, 50-85, 50-90, 50-95, 50-99, 55-60, 55-55 ~65, 55~70, 55~75, 55~80, 55~85, 55~90, 55~95, 55~99, 60~65, 60~70, 60~75, 60~80, 60~85, 60~90, 60~95, 60~99, 65~70, 65~75, 65~80, 65~85, 65~90, 65~95, 65~99, 70~80, 70~85, 70~90, 70~95, 70~99, 80~85, 80~90, 80~95, 80~99, 80~100,.
[0092] In the above “100<T2≤250”, the value of T2 includes the minimum value and the maximum value of the range, and every value between the minimum value and the maximum value. Specific examples include but are not limited to the point values in the embodiment and the following point values: “101, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250; or a range consisting of any two values, for example: 101-120, 101-150, 101-160, 101-170, 101-180, 101-200, 101-220, 101-250, 1 10-120, 110-150, 110-160, 110-170, 110-180, 110-200, 110-220, 110-250, 120-150, 120-160, 120-170, 120-180, 120-200, 120-220, 120-250, 130-150, 130-160, 130-170, 130-180, 130-200, 130-220, 130-250, 150-160, 150-170, 150-180, 150-200, 150-220, 150-250.
[0093] In the above “250<T3≤600”, the value of T3 includes the minimum value and the maximum value of the range, and every value between the minimum value and the maximum value. Specific examples include but are not limited to the point values in the embodiment and the following point values: “260, 300, 350, 400, 450, 500, 550, 600; or a range consisting of any two values, for example: 260-300, 260-350, 260-400, 260-450, 260-500, 2 60~550, 300~350, 300~400, 300~450, 300~500, 300~550, 300~600, 350~400, 350~450, 350~500, 350~550, 350~600, 400~450, 400~500, 400~550, 400~600, 450~500, 450~550, 450~600, 500~550, 500~600.
[0094] In some of the embodiments, the mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer is (1-2): (1-4): (3-6).
[0095] In some of the embodiments, the mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer is 1:(1-4):(5-6).
[0096] By adjusting the mass ratio of three liquid-retaining polymers with different molecular weights, the cycle performance and rate of the battery can be further improved.
[0097] In the above “(1~2):(1~4):(3~6)”, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 1:1:5, 1:1:3, 1:1:4, 1:1:6, 1:2:5, 1:3:5, 2:2:5, 2:3:5, 1:2:6, 1:3:6, 2:2:6, 2:3:6.
[0098] In some of these embodiments, at least one liquid retaining polymer contains lithium ions.
[0099] The presence of lithium ions can further increase the migration rate of lithium ions between the positive and negative electrodes. The molecular chain of the liquid-retaining polymer contains lithium ions, that is, the lithium ions are connected to other elements on the molecular chain of the liquid-retaining polymer through chemical bonds. In this way, lithium ions are not easy to leak, which effectively increases the migration rate of lithium ions between the positive and negative electrodes, thereby improving the cycle performance and rate of the battery.
[0100] Optionally, based on the mass of the liquid retaining polymer, the mass proportion of lithium ions is 0.2% to 15%.
[0101] By regulating the mass ratio of lithium ions in the liquid-retaining polymer, the migration rate of lithium ions between the positive and negative electrodes can be further improved, thereby improving the cycle performance and rate of the battery.
[0102] In the above “0.2%~15%”, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: “0.2%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%; or a range consisting of any two values, for example: 0.2%~15%, 0.2%~14%, 0.2%-13%, 0.2%-12%, 0.2%-11%, 0.2%-10%, 0.2%-8%, 0.2%-7%, 0.2%-6%, 0.2%-5%, 0.2%-4%, 0.2%-3%, 0.2%-2%, 0.2%-1%, 5%-15%, 5%-13%, 5%-10%, 5%-9%, 5%-7%, 6%-15%, 6%-13%, 6%-10%, 6%-9%, 6%-7%, 8%-15%, 8%-13%, 8%-10%, 8%-9%, 10%-15%, 10%-13%.
[0103] In some of the embodiments, at least one liquid retaining polymer has lithium ions on side groups of its molecular chain.
[0104] It can be understood that the molecular chain of the liquid-retaining polymer includes a main chain and side groups connected to the main chain, and a chemical bond is formed between the lithium ions and the group atoms on the side groups.
[0105] In some of the embodiments, the mass ratio of the liquid retaining polymer containing lithium ions to the liquid retaining polymer not containing lithium ions is 10:(2-5).
[0106] In the above “10: (2-5)”, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiment and the following point values: “10: 2, 10: 3, 10: 4, 10: 5; or a range consisting of any two values.
[0107] It should be noted that the molecular weights of the liquid-retaining polymer containing lithium ions and the liquid-retaining polymer not containing lithium ions may be the same or different.
[0108] In some of the embodiments, in the active layer, the total mass proportion of the liquid retaining polymer is 0.3% to 0.8%.
[0109] In some of the embodiments, in the active layer, the total mass proportion of the liquid retaining polymer is 0.3% to 0.5%.
[0110] Regulate the amount of liquid-retaining polymer used to reduce the chance of gel formation during preparation, leading to decreased electrode uniformity.
[0111] In the above-mentioned "0.3%~0.8%", the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%; or a range consisting of any two numerical values, for example: 0.3%~0.8%, 0.3%~0.7%, 0.3%~0.6%, 0.3%~0.5%, 0.3%~0.4%, 0.4%~0.8%, 0.4%~0.7%, 0.4%~0.6%, 0.4%~0.5%, 0.5%~0.8%, 0.5%~0.7%, 0.5%~0.6%.
[0112] In some embodiments, the functional group includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group and an ether bond.
[0113] In some embodiments, each liquid retaining polymer contains the same functional group.
[0114] In some embodiments, each liquid-retaining polymer has a main chain with the same structure; further, the main chain is selected from any one of a polyethylene glycol main chain, a polyvinyl alcohol main chain and a polyacrylic acid main chain.
[0115] It can be understood that the main chain of a polymer is composed of repeating units arranged in a chain structure, which is the polymer skeleton.
[0116] In some of the embodiments, non-limiting examples of the liquid-retaining polymer containing lithium ions include at least one of polyvinyl alcohol-lithiation and polyacrylic acid-lithiation.
[0117] In some of the embodiments, the liquid-retaining polymer includes at least one of polyvinyl alcohol free of lithium ions, polyvinyl alcohol containing lithium ions, polyethylene glycol free of lithium ions, polyethylene glycol containing lithium ions, polyacrylic acid free of lithium ions, polyacrylic acid containing lithium ions, polyvinyl alcohol-acrylic acid graft polymer free of lithium ions, polyvinyl alcohol-acrylic acid graft polymer containing lithium ions, polyethylene glycol acrylate free of lithium ions, polyethylene glycol acrylate containing lithium ions, polyethylene glycol diacrylate free of lithium ions, polyethylene glycol diacrylate containing lithium ions, polyethylene glycol acrylate free of lithium ions, and polyethylene glycol acrylate containing lithium ions.
[0118] In some embodiments, the active layer further comprises a binder.
[0119] Optionally, in the active layer, the total mass proportion of the binder is 0.8% to 4%.
[0120] In the above "0.8%~4%", the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%; or a range consisting of any two values.
[0121] In some embodiments, the binder includes a carboxymethyl cellulose binder. In the active layer, the total mass of the carboxymethyl cellulose binder and the liquid-retaining polymer accounts for 1% to 2%.
[0122] Optionally, the total mass proportion of the carboxymethyl cellulose binder and the liquid retaining polymer is 1% to 1.5%.
[0123] By controlling the amount of carboxymethyl cellulose binder, it can work synergistically with the liquid-retaining polymer to maintain good liquid-retaining performance while maintaining good bonding performance to reduce the probability of electrode cracking.
[0124] In the above "1%~2%", the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%; or a range consisting of any two values.
[0125] In some embodiments, the adhesive further comprises a styrene-butadiene rubber adhesive.
[0126] Optionally, in the active layer, the mass proportion of the styrene-butadiene rubber binder is 1% to 1.8%.
[0127] In the above "1%~1.8%", the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and the following point values: 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%; or a range consisting of any two values.
[0128] In some embodiments, the carboxymethyl cellulose-based binder includes at least one of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
[0129] In some of these embodiments, the molecular weight of the binder is different from the molecular weight of the liquid retaining polymer.
[0130] Optionally, the number average molecular weight of the binder is greater than the molecular weight of the liquid retaining polymer.
[0131] Further optionally, the number average molecular weight of the binder is ≥ 100,000.
[0132] In some embodiments, the components of the active layer further include a negative electrode active material and a negative electrode conductive agent.
[0133] In any embodiment of the present application, the above-mentioned negative electrode active material includes at least one of mesophase carbon microbeads, graphite, glassy carbon, carbon nanotubes, carbon-carbon composite materials, carbon fibers, hard carbon, soft carbon, silicon-based materials, tin-based materials, magnesium-based materials, and iron-based materials.
[0134] Optionally, specific examples of the above-mentioned negative electrode active materials include, but are not limited to: at least one of interphase carbon microspheres, natural graphite, artificial graphite, graphene, glassy carbon, carbon nanotubes, carbon fibers, hard carbon, soft carbon, iron oxide, tin oxide, silicon oxide, magnesium oxide, and silicon-carbon composites.
[0135] In any embodiment of the present application, the mass proportion of the negative electrode active material in the active layer is 70% to 99.5%.
[0136] In any embodiment of the present application, the above-mentioned negative electrode conductive agent can be a conductive material commonly used in the art, including but not limited to: at least one of graphite, carbon nanotubes, nanofibers, carbon black and graphene. Specifically, it can be selected from SP, KS-6, acetylene black, branched Ketjen black ECP, SFG-6, vapor-grown carbon fiber VGCF, carbon nanotubes CNTs and graphene and their composite conductive agents.
[0137] In some embodiments, the weight ratio of the negative electrode conductive agent in the active layer is 0.05% to 20%.
[0138] In any embodiment of the present application, the current collector in the negative electrode sheet may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil.
[0139] The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate.
[0140] In some embodiments, the metal material is selected from any one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.
[0141] In some of the embodiments, the polymer material substrate includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0142] In one embodiment of the present application, a method for preparing a negative electrode sheet is provided, comprising the following step S10.
[0143] Step S10: using active slurry to form an active layer on the surface of the current collector to prepare a negative electrode sheet; the components of the active slurry include at least two liquid-retaining polymers with different molecular weights; the liquid-retaining polymer contains functional groups that can form hydrogen bonds with water.
[0144] The selection of the liquid retaining polymer is the same as described above and will not be repeated here.
[0145] In any embodiment of the present application, the negative electrode sheet can be prepared by the following method: the above components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the liquid retaining polymer, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s
[0146] ~10000mPa·s; coating the obtained negative electrode slurry on the negative electrode collector, and undergoing a drying process, cold pressing such as rolling to obtain a negative electrode sheet.
[0147] In some embodiments, the surface density of the negative electrode active material contained in the negative electrode sheet is 0.005 g / cm 2 ~0.03g / cm 2 .
[0148] The surface density of the negative electrode active material = the mass of the negative electrode active material / the area of the negative electrode sheet.
[0149] According to one embodiment of the present application, a battery is provided, wherein the battery includes the negative electrode sheet as described above or the negative electrode sheet prepared by the method for preparing the negative electrode sheet as described above.
[0150] The battery has excellent cycle performance and rate performance.
[0151] The battery further includes a positive electrode sheet, a separator and an electrolyte. Examples of the positive electrode sheet, the separator and the electrolyte are described below, including but not limited to the following.
[0152] [Positive electrode]
[0153] The positive electrode sheet includes a current collector and a positive electrode active layer arranged on the surface of the current collector, and the components of the positive electrode active layer include positive electrode active materials.
[0154] As an example, the current collector in the positive electrode sheet has two surfaces opposite to each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0155] In any embodiment of the present application, the current collector in the positive electrode sheet may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material on a polymer material substrate.
[0156] In some embodiments, the metal material includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.
[0157] In some of the embodiments, the polymer material substrate includes at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0158] The positive electrode active material may be a commonly used positive electrode active material in the present application, such as a lithium ion positive electrode active material or a sodium ion positive electrode active material.
[0159] Further, as an example, the lithium ion active material may include at least one of the following materials: lithium phosphates containing olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium manganese phosphate (such as LiMnPO4), and lithium manganese iron phosphate.
[0160] In any embodiment of the present application, the molecular formula of the lithium ion active material is: LiFe x Mn (1-x) PO4, x can be any number from 0 to 1.
[0161] It can be understood that when x is 0, LiFe x Mn (1-x) PO4 is LiMnPO4 lithium manganese phosphate, and when x is 1, LiFePO4 is LiFePO4 lithium iron phosphate (LFP).
[0162] It should be noted that the lithium content in the positive electrode material exemplified above refers to its content when it is not in use. During the use of the battery, it will be repeatedly used as a battery, accompanied by the deintercalation and consumption of Li. The Li in the positive electrode active material will change during the charge and discharge process, that is, the molar subscript of Li in the positive electrode active material in the battery product will not always remain at 1, but will change; further, the range of change may be (0 to 1.2). In the enumeration of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode material is used in the battery system, and after the charge and discharge cycle, the molar content of Li will change.
[0163] Similarly, in the list of positive electrode materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0164] For example, LiFe x Mn (1-x) PO4 can be further expressed as Li y Fe x Mn (1-x) PO4, y is 0~1.1.
[0165] For example, for the ternary material Li y (Ni a Co b Mn c ) 1-d M d O 2-x A z , y is 0.2~1.2, a+b+c=1, 0≤d≤1, 0≤x<2; M is one or more of Zr, Sr, B, Ti, Mg, Sn and Al, and A is one or more of S, N, F, Cl, Br and I.
[0166] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process. The molar content of Li is different when the battery is discharged to different states. The above definition of y includes the molar content of Li under different charge and discharge states of the battery; further, the battery voltage is usually between 2-5V.
[0167] As an example, the sodium ion active material may include at least one of the following materials: at least one of a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0168] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal includes at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M includes at least one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.
[0169] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. Transition metals include at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y includes at least one of P, S and Si; n represents (YO4) n- valence state.
[0170] Polyanionic compounds can also be those with sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal includes at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y includes at least one of P, S and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.
[0171] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedral unit (ZO y ) m+ and a class of compounds containing an optional halogen anion. Y includes at least one of P, S and Si, and n represents (YO4) n- valence state; Z represents a transition metal, including at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.
[0172] Polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2 (P2O7), NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).
[0173] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ). The transition metal includes at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' each independently include at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0174] The weight ratio of the positive electrode active material in the positive electrode active layer is 80 wt % to 100 wt % based on the total weight of the positive electrode active layer.
[0175] In any embodiment of the present application, the components of the positive electrode active layer further include a positive electrode conductor and a positive electrode binder.
[0176] The positive electrode conductive agent can be a conductive agent commonly used in the art, including but not limited to: at least one of graphite, carbon nanotubes, nanofibers, carbon black and graphene. Specifically, it can be selected from SP, KS-6, acetylene black, branched Ketjen black ECP, SFG-6, vapor-grown carbon fiber VGCF, carbon nanotubes CNTs and graphene and their composite conductive agents.
[0177] The weight ratio of the positive electrode conductive agent in the positive electrode active layer is 0 to 20 wt % based on the total weight of the positive electrode active layer.
[0178] In any embodiment of the present application, the binder of the above-mentioned positive electrode binder can be polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, hydrogenated nitrile rubber, styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), carboxymethyl chitosan (CMCS) and at least one of fluorine-containing acrylate resins.
[0179] The weight ratio of the positive electrode binder in the positive electrode active layer is 0 to 30 wt % based on the total weight of the positive electrode active layer.
[0180] In any embodiment of the present application, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The solid content of the positive electrode slurry is 40wt% to 80wt%, and the viscosity at room temperature is adjusted to 5000mPa·s
[0181] ~25000mPa·s, the positive electrode slurry is coated on the surface of the positive electrode current collector, and after drying, it is cold-pressed by a cold rolling mill to form a positive electrode sheet; the unit surface density of the positive electrode powder coating is 15-35mg / cm 2 The compaction density of the positive electrode is 3.0-3.6 g / cm 3 , can be selected as 3.3~3.5g / cm 3 The calculation formula for compacted density is:
[0182] Compacted density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0183] [Electrolyte]
[0184] The electrolyte includes electrolyte salt and solvent
[0185] In some embodiments, the electrolyte salt may be selected from electrolyte salts commonly used in the art, such as lithium ion electrolyte salts.
[0186] As an example, the lithium ion electrolyte salt includes, but is not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0187] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0188] In some embodiments, in the electrolyte solution, the concentration of the electrolyte salt is generally 0.5 mol / L to 15 mol / L.
[0189] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0190] [Isolation film]
[0191] The separator is arranged between the positive electrode sheet and the negative electrode sheet.
[0192] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0193] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0194] The thickness of the diaphragm is controlled within a range of 2 μm to 15 μm; optionally, the thickness of the diaphragm is controlled within a range of 2 μm to 13 μm.
[0195] In some embodiments, the battery is a secondary battery; specifically, the battery is a lithium-ion battery.
[0196] The shape of the battery of the present application is not particularly limited, and it can be cylindrical, square or any other shape. For example, Figure 1 The battery 4 is a square structure as an example.
[0197] In some embodiments, reference Figure 2 The housing may include a shell 41 and a cover plate 43. The shell 41 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 41 has an opening connected to the receiving cavity, and the cover plate 43 can be covered on the opening to close the receiving cavity.
[0198] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly 42. The electrode assembly 42 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 42. The number of electrode assemblies 42 included in the battery 4 can be one or more, which can be adjusted according to needs.
[0199] The present application also provides an electrical device, which includes the above-mentioned battery.
[0200] Furthermore, in the above-mentioned electrical device, the battery may exist in the form of a battery cell, or may be further assembled into a battery pack.
[0201] Figure 3 and Figure 4 The battery pack 1 is used as an example. The battery pack 1 includes a battery box and one or more batteries 4 arranged in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can be covered on the lower box body 3 and form a closed space for the battery 4.
[0202] The multiple batteries 4 can be arranged in the battery box in any manner.
[0203] The above-mentioned battery or the battery pack assembled therefrom can be used as a power source for an electrical device, and can also be used as an energy storage unit for an electrical device.
[0204] The above-mentioned electrical devices may be, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0205] Figure 5 The power consumption device 5 is taken as an example. The power consumption device 5 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device 5's requirements for high power and high energy density of the battery, a battery pack can be used.
[0206] As another example, the power-consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a battery may be used as a power source.
[0207] The present application will be described below in conjunction with specific embodiments, but the present application is not limited to the following embodiments. It should be understood that the attached claims summarize the scope of the present application. Under the guidance of the concept of the present application, technical personnel in the field should realize that certain changes made to the various embodiments of the present application will be covered by the spirit and scope of the claims of the present application.
[0208] The following are specific embodiments.
[0209] Example 1
[0210] S1. Preparation of positive electrode sheet: Prepare positive electrode slurry according to the following method:
[0211] The ternary positive electrode active material NCM532, the conductive agent acetylene black, and the binder PVDF were added into a vacuum mixer in a mass ratio of 96:2:2 for mixing, and then the solvent NMP was added into the mixed slurry. The mixed slurry was stirred into a uniform state under the action of the vacuum mixer, thereby obtaining a positive electrode slurry.
[0212] The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying. After drying in the oven, a positive electrode active layer is formed, which is then cold pressed and cut to obtain a positive electrode sheet to be assembled. The thickness of the positive electrode active layer is 109 μm.
[0213] S2. Preparation of negative electrode sheet:
[0214] The negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid-retaining polymer are added to a vacuum mixer at a mass ratio of 96.8:0.7:1.5:0.5:0.5 for mixing, and then the solvent deionized water is added to the mixed slurry, and the mixed slurry is stirred to a uniform state under the action of the vacuum mixer to obtain the negative electrode slurry, and observe whether the slurry has a gel phenomenon. Among them, in the liquid-retaining polymer, the mass proportions of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 600, and polyethylene glycol lithium with a number average molecular weight of 600 are 25%, 25%, 25%, and 25%, respectively.
[0215] The above negative electrode slurry is evenly coated on the two surfaces of the negative electrode current collector copper foil, dried at room temperature and then transferred to an oven for further drying. After drying in the oven, a negative electrode active layer is formed, which is then cold pressed into a pole sheet with a thickness of 131 μm, cut to obtain a negative electrode sheet, and observe whether the negative electrode sheet has cracking.
[0216] Characterization test of negative electrode sheet: The active layer in the negative electrode sheet was split, and the binder and liquid-retaining polymer were separated by scraping powder-hydrothermal ultrasound-centrifugation-filtration. The mass proportion of each component was weighed and calculated, among which the mass proportion of liquid-retaining polymer in the active layer was recorded as H1, and the total mass proportion of carboxymethyl cellulose binder and liquid-retaining polymer in the active layer was recorded as H2.
[0217] The liquid retaining polymer was subjected to infrared spectroscopy, and the types of functional groups contained in the liquid retaining polymer were confirmed based on characteristic peaks. Please see Table 1 for details.
[0218] The liquid-retaining polymer is subjected to a gel chromatography test to obtain its gel chromatography elution curve. The two peaks in the curve are calculated using software to obtain the molecular weights corresponding to the two peaks, namely, the first liquid-retaining polymer with a number average molecular weight of T1 and the third liquid-retaining polymer with a number average molecular weight of T3. The integrated area ratio of the two peaks is further obtained through integration and homogenization, which is the mass ratio Y1 of the first liquid-retaining polymer and the third liquid-retaining polymer.
[0219] The liquid retaining polymer is tested by flame atomic absorption spectrometry to analyze and calculate the mass proportion Y2 of lithium ions in the liquid retaining polymer.
[0220] Please see Table 1 for specific parameters.
[0221] S3. Preparation of electrolyte
[0222] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of EC:EMC:DEC=1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0223] S4. Isolation membrane: A polyethylene membrane is selected as the isolation membrane for lithium-ion batteries.
[0224] S5. Assembly of lithium-ion batteries: stack the positive electrode sheet, isolation film, and negative electrode sheet to be assembled in sequence, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then obtain a bare battery cell by winding; place the bare battery cell in a battery casing, inject electrolyte after drying, and obtain the lithium-ion battery to be tested through vacuum packaging, standing, forming, shaping and other processes.
[0225] S6. Performance test of lithium-ion batteries
[0226] 1. At 25°C, the lithium-ion battery used as the test object is cycled according to the following procedure: fully charge at a 1C rate, let it stand for 30 minutes, and then fully discharge it, which is considered as one cycle. The initial capacity at this time is recorded. This cycle is repeated for 1500 cycles, and the remaining capacity of the battery is recorded. The percentage of the remaining capacity to the initial capacity is recorded as P.1500 .
[0227] 2. Equivalent rate test: use the three-electrode detection method to test the battery's 30% to 80% equivalent window at 25°C.
[0228] 3. Low temperature lithium deposition test: Use -10℃ battery charging window, cycle the battery cell for 10 times at 1.1 times magnification, and disassemble the battery cell to confirm the lithium deposition of the negative electrode.
[0229] Example 2
[0230] Example 2 is basically the same as Example 1, with the only difference being that in step S2, in the liquid-retaining polymer, the mass proportions of polyethylene glycol with a number average molecular weight of 50, polyethylene glycol lithium with a number average molecular weight of 50, polyethylene glycol with a number average molecular weight of 500, and polyethylene glycol lithium with a number average molecular weight of 500 are 25%, 25%, 25%, and 25%, respectively.
[0231] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0232] Example 3
[0233] Example 3 is basically the same as Example 1, with the only difference being that in step S2, in the liquid-retaining polymer, the mass proportions of polyethylene glycol with a number average molecular weight of 100, polyethylene glycol lithium with a number average molecular weight of 100, polyethylene glycol with a number average molecular weight of 450, and polyethylene glycol lithium with a number average molecular weight of 450 are 25%, 25%, 25%, and 25%, respectively.
[0234] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0235] Example 4
[0236] Example 4 is basically the same as Example 1, with the only difference being that in step S2, in the liquid-retaining polymer, the mass proportions of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 300, and polyethylene glycol lithium with a number average molecular weight of 300 are 25%, 25%, 25%, and 25%, respectively.
[0237] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0238] Example 5
[0239] Example 5 is basically the same as Example 1, with the only difference being that in step S2, in the liquid-retaining polymer, the mass proportions of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 600, and polyethylene glycol lithium with a number average molecular weight of 600 are 7%, 7.5%, 42.5%, and 43%, respectively.
[0240] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0241] Example 6
[0242] Example 6 is basically the same as Example 1, with the only difference being that in step S2, in the liquid-retaining polymer, the mass proportions of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 600, and polyethylene glycol lithium with a number average molecular weight of 600 are 12.5%, 12.5%, 37.5%, and 37.5%, respectively.
[0243] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0244] Example 7
[0245] Example 7 is substantially the same as Example 1, except that in step S2, in the liquid retaining polymer, the weight proportions of polyethylene glycol with a number average molecular weight of 80 and polyethylene glycol with a number average molecular weight of 500 are 50% and 50% respectively.
[0246] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0247] Example 8
[0248] Example 8 is basically the same as Example 1, except that: in step S2, the negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid-retaining polymer are added to a vacuum mixer at a mass ratio of 96.8:0.7:1.5:0.5:0.5 for mixing, and then the solvent deionized water is added to the mixed slurry, and the mixed slurry is stirred to a uniform state under the action of the vacuum mixer, thereby obtaining a negative electrode slurry, and observing whether the slurry has a gel phenomenon. Among them, the liquid-retaining polymer includes polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 200, polyethylene glycol lithium with a number average molecular weight of 200, polyethylene glycol with a number average molecular weight of 500, and polyethylene glycol lithium with a number average molecular weight of 500, and the mass proportions in the liquid-retaining polymer are 5%, 5%, 20%, 20%, 25%, and 25%, respectively.
[0249] Correspondingly, there are three peaks in the gel chromatography elution curve of the liquid-retaining polymer, namely, the first liquid-retaining polymer with a number average molecular weight of T1, the second liquid-retaining polymer with a number average molecular weight of T2, and the third liquid-retaining polymer with a number average molecular weight of T3; at this time, Y1 is the mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer.
[0250] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0251] Example 9
[0252] Example 9 is basically the same as Example 8, except that: in step S2, the mass ratio of the negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid retaining polymer is 96.3:0.7:1.5:1.2:0.3, and in the liquid retaining polymer, the mass ratio of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 200, polyethylene glycol lithium with a number average molecular weight of 200, polyethylene glycol with a number average molecular weight of 500, and polyethylene glycol lithium with a number average molecular weight of 500 is 1%:9%:4%:36%:5%:45%.
[0253] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0254] Example 10
[0255] Example 10 is basically the same as Example 9, with the only difference being that in step S2, in the liquid-retaining polymer, the mass ratios of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 200, polyethylene glycol lithium with a number average molecular weight of 200, polyethylene glycol with a number average molecular weight of 500, and polyethylene glycol lithium with a number average molecular weight of 500 are 1.4%, 12.9%, 1.4%, 12.9%, 7.1%, and 64.3%, respectively.
[0256] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0257] Embodiment 11
[0258] Example 11 is basically the same as Example 10, except that in step S2, the mass ratio of the negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid retaining polymer is 96.3:0.7:1.5:1.2:0.3, and in the liquid retaining polymer, the mass ratios of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 200, polyethylene glycol lithium with a number average molecular weight of 200, polyethylene glycol with a number average molecular weight of 500, and polyethylene glycol lithium with a number average molecular weight of 500 are 5.0%, 7.5%, 12.5%, 12.5%, 18.8%, and 43.7%.
[0259] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0260] Example 12
[0261] Example 12 is basically the same as Example 9, except that in step S2, the mass ratio of the negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid retaining polymer is 96.8:0.7:1.5:0.5:0.5. In the liquid retaining polymer, the mass ratio of polyethylene glycol with a number average molecular weight of 90, lithium polyethylene glycol with a number average molecular weight of 90, polyethylene glycol with a number average molecular weight of 250, lithium polyethylene glycol with a number average molecular weight of 250, polyethylene glycol with a number average molecular weight of 600, and lithium polyethylene glycol with a number average molecular weight of 600 is 4.0%, 6.0%, 20.0%, 20.0%, 15.0%, and 35.0%.
[0262] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0263] Embodiment 13
[0264] Example 13 is basically the same as Example 9, except that in step S2, the mass ratio of negative electrode active material graphite, conductive agent acetylene black, styrene-butadiene latex, sodium carboxymethyl cellulose, and liquid retaining polymer is 96.8:0.7:1.5:0.5:0.5, and in the liquid retaining polymer, the mass ratio of polyvinyl alcohol with a number average molecular weight of 90, lithium polyvinyl alcohol with a number average molecular weight of 90, polyvinyl alcohol with a number average molecular weight of 250, lithium polyvinyl alcohol with a number average molecular weight of 250, polyvinyl alcohol with a number average molecular weight of 600, and lithium polyvinyl alcohol with a number average molecular weight of 600 is 4.0%, 6.0%, 20.0%, 20.0%, 15.0%, and 35.0%.
[0265] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0266] Embodiment 14
[0267] Example 14 is basically the same as Example 9, except that in step S2, the mass ratio of negative electrode active material graphite, conductive agent acetylene black, styrene butadiene latex, lithium carboxymethyl cellulose, and liquid retaining polymer is 96.8:0.7:1.5:0.5:0.5, and in the liquid retaining polymer, the mass ratio of polyacrylic acid with a number average molecular weight of 90, lithium polyacrylate with a number average molecular weight of 90, polyacrylic acid with a number average molecular weight of 250, lithium polyacrylate with a number average molecular weight of 250, polyacrylic acid with a number average molecular weight of 600, and lithium polyacrylate with a number average molecular weight of 600 is 4.0%, 6.0%, 20.0%, 20.0%, 15.0%, and 35.0%.
[0268] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0269] Embodiment 15
[0270] Example 15 is basically the same as Example 10, except that in step S2, the mass ratio of the negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid retaining polymer is 96.3:0.7:1.5:1.2:0.3, and in the liquid retaining polymer, the mass proportions of polyethylene glycol with a number average molecular weight of 80, polyethylene glycol lithium with a number average molecular weight of 80, polyethylene glycol with a number average molecular weight of 200, polyethylene glycol lithium with a number average molecular weight of 200, polyethylene glycol with a number average molecular weight of 500, and polyethylene glycol lithium with a number average molecular weight of 500 are 4.0%, 6.0%, 15.0%, 15.0%, 18.0%, and 42.0%, respectively.
[0271] Comparative Example 1
[0272] Comparative Example 1 is substantially the same as Example 1, except that in step S2, no liquid-retaining polymer is added to the negative electrode slurry, and the negative electrode active material graphite, the conductive agent acetylene black, styrene-butadiene latex and sodium carboxymethyl cellulose are mixed in a mass ratio of 96.8:0.7:1.5:1.
[0273] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0274] Comparative Example 2
[0275] Comparative Example 2 is basically the same as Example 1, except that in step S2, the mass ratio of the negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid retaining polymer is 96.8:0.7:1.5:0.5:0.5, and the liquid retaining polymer is polyethylene glycol with a number average molecular weight of 500.
[0276] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0277] Comparative Example 3
[0278] Comparative Example 3 is basically the same as Example 1, except that in step S2, the mass ratio of the negative electrode active material graphite, the conductive agent acetylene black, styrene butadiene latex, sodium carboxymethyl cellulose, and the liquid retaining polymer is 96.8:0.7:1.5:0.5:0.5, and the liquid retaining polymer is polyethylene glycol with a number average molecular weight of 80.
[0279] The other steps are the same as those in implementation 1. For specific parameters, see Table 1.
[0280] The relevant parameters and performance test results of each embodiment and comparative example are shown in Table 1. The proportion of the liquid-retaining polymer in the active layer is recorded as H1, the total mass proportion of the carboxymethyl cellulose binder and the liquid-retaining polymer in the active layer is recorded as H2, the mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer is Y1, and the mass proportion of lithium ions in the liquid-retaining polymer in the active layer is Y2.
[0281] Table 1
[0282]
[0283] “ / ” indicates that the substance or parameter does not exist.
[0284] By comparing and analyzing the data of Comparative Examples 1 to 3 in Table 1 and Examples 1 to 13 using the solution of the present application, it can be seen that the technical solution of the present application and the combination of liquid-retaining polymers with different molecular weights can improve the cycle performance and charging rate of the battery. Comparative Example 2 uses high molecular weight liquid-retaining polymers. Although it can improve the liquid retention capacity, the swelling after absorbing liquid will block the lithium ion channel, resulting in deterioration of the charging capacity and cycle performance. Comparative Example 3 uses small molecular weight liquid-retaining polymers, the charging window is deteriorated, and the lithium precipitation situation is significantly deteriorated.
[0285] Furthermore, by comparing and analyzing the data of Examples 1 to 7 and Examples 9 to 15, it can be seen that regulating the molecular weight of each level of the liquid retaining polymer and its mass ratio can further improve the cycle performance and rate of the battery.
[0286] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0287] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description and drawings may be used to interpret the contents of the claims.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector and an active layer disposed on the surface of the current collector, wherein the components of the active layer comprise at least two liquid-retaining polymers having different molecular weights; The liquid retaining polymer contains functional groups that can form hydrogen bonds with water.
2. The negative electrode sheet according to claim 1, characterized in that: The liquid-retaining polymer in the active layer has at least two peaks in its gel chromatography elution curve.
3. The negative electrode sheet according to claim 2, characterized in that: In the gel chromatography elution curve, the number average molecular weight corresponding to each peak is independently selected from 50 to 600; Optionally, the number average molecular weight corresponding to at least one peak is 50-100, and the number average molecular weight corresponding to at least another peak is 300-600.
4. The negative electrode sheet according to claim 3, characterized in that: The mass ratio of the liquid retaining polymer having a number average molecular weight of 50 to 100 to the liquid retaining polymer having a number average molecular weight of 300 to 600 is 1:(1 to 6).
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The gel chromatography elution curve of the liquid-retaining polymer in the active layer contains three peaks.
6. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The active layer includes a first liquid-retaining polymer with a number average molecular weight of T1, a second liquid-retaining polymer with a number average molecular weight of T2, and a third liquid-retaining polymer with a number average molecular weight of T3; Among them, 50≤T1≤100, 100<T2≤250, 250<T3≤600; optionally, 500≤T3≤600.
7. The negative electrode sheet according to claim 6, characterized in that: The mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer is (1-2): (1-4): (3-6); Optionally, a mass ratio of the first liquid-retaining polymer, the second liquid-retaining polymer and the third liquid-retaining polymer is 1:(1-4):(5-6).
8. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: At least one liquid retaining polymer contains lithium ions; Optionally, based on the mass of the liquid retaining polymer, the mass proportion of the lithium ions is 0.2% to 15%.
9. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: At least one of the liquid-retaining polymers has lithium ions on its side groups in its molecular chain; Optionally, the mass ratio of the liquid-retaining polymer containing lithium ions to the liquid-retaining polymer not containing lithium ions is 10:(2-5).
10. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: In the active layer, the total mass of the liquid-retaining polymer accounts for 0.3% to 0.8%; Optionally, in the active layer, the total mass proportion of the liquid-retaining polymer is 0.3% to 0.5%.
11. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The liquid-retaining polymer satisfies at least one of the following conditions (I) to (II): (I) the functional group includes at least one of a hydroxyl group, a carboxyl group, a carbonyl group and an ether bond; Optionally, each of the liquid-retaining polymers contains the same functional group; (II) each of the liquid-retaining polymers has a main chain with the same structure; Optionally, the main chain is selected from any one of a polyethylene glycol main chain, a polyvinyl alcohol main chain and a polyacrylic acid main chain.
12. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The liquid-retaining polymer includes at least one of polyvinyl alcohol free of lithium ions, polyvinyl alcohol containing lithium ions, polyethylene glycol free of lithium ions, polyethylene glycol containing lithium ions, polyacrylic acid free of lithium ions, polyacrylic acid containing lithium ions, polyvinyl alcohol-acrylic acid graft polymer free of lithium ions, polyvinyl alcohol-acrylic acid graft polymer containing lithium ions, polyethylene glycol acrylate free of lithium ions, polyethylene glycol acrylate containing lithium ions, polyethylene glycol diacrylate free of lithium ions, polyethylene glycol diacrylate containing lithium ions, polyethylene glycol acrylate free of lithium ions, and polyethylene glycol acrylate containing lithium ions.
13. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The components of the active layer also include a binder; Optionally, the binder includes a carboxymethyl cellulose binder, and in the active layer, the total mass of the carboxymethyl cellulose binder and the liquid-retaining polymer accounts for 1% to 2%; Further optionally, the total mass proportion of the carboxymethyl cellulose binder and the liquid retaining polymer is 1% to 1.5%.
14. The negative electrode sheet according to claim 13, wherein the molecular weight of the binder is different from the molecular weight of the liquid retaining polymer; Optionally, the number average molecular weight of the binder is greater than the molecular weight of the liquid retaining polymer; Further optionally, the number average molecular weight of the binder is ≥ 100,000.
15. A method for preparing a negative electrode sheet, characterized in that: The steps include: An active layer is formed on the surface of a current collector using an active slurry to prepare a negative electrode sheet; The components of the active slurry include at least two liquid-retaining polymers with different molecular weights; the liquid-retaining polymers contain functional groups that can form hydrogen bonds with water.
16. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in any one of claims 1 to 14 or the negative electrode sheet prepared by the method for preparing the negative electrode sheet as claimed in claim 15.
17. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 16.
Citation Information
Patent Citations
Cell, battery, liquid-preserving coating, battery pole piece and preparation method thereof
CN110071293A
Composition for electrodes, electrode sheet for all-solid-state secondary batteries, all-solid-state secondary battery, and method for producing electrode sheet for all-solid-state secondary batteries or all-solid-state secondary battery
CN112640161A
Polymer secondary battery and its manufacturing method
JP2002158037A
Slurry composition for negative electrode for lithium ion secondary battery, manufacturing method for negative electrode for lithium ion secondary battery, and lithium ion secondary battery
WO2015033827A1
Cited By
Negative electrode slurry, negative electrode sheet, and battery
WO2026145724A1
